Valproic acid potentiates curcumin-mediated neuroprotection in lipopolysaccharide induced rats - Zaky, Amira; Mahmoud, Mariam; Awad, Doaa; El Sabaa, Bassma M.; Kandeel, Kamal M.; Bassiouny, Ahmad R. (Frontiers in Cellular Neuroscience, 2014)
The etiology of neuroinflammation is complex and comprises multifactorial, involving both genetic and environmental factors during which diverse genetic and epigenetic modulations are implicated. Curcumin (Cur), and valproic acid (VPA), histone deacetylase 1 inhibitor, have neuroprotective effects. The present study was designed with an aim to investigate the ability of co-treatment of both compounds (Cur or VPA (200mg/kg) for four weeks to augment neuroprotection and enhance brain recovery from intra-peritoneal (IP) injection of (250 µg/kg) lipopolysaccharide (LPS)-stimulated neuroinflammatory condition on rat brain cortex. Cortex activation and the effects of combined treatment and production of proinflammatory mediators, COX-2, APE1 and nitric oxide/iNOS were investigated. Neuroinflammation development was assessed by histological analyses and by investigating associated indices (BACE1, APP, PSEN-1 and PSEN-2). Furthermore we measured the expression profile of let-7 miRNAs members a, b, c, e and f in all groups, a highly abundant regulator of gene expression in the CNS. Protein and mRNA levels of neuroinflammation markers COX-2, BACE1, APP and iNOS were also attenuated by combined therapy. On the other hand, assessment of the indicated five let-7 members, showed distinct expression profile pattern in the different groups. Let-7 a, b and c disappeared in the induced group, an effect that was partially suppressed by co-addition of either Cur or VPA. These data suggest that the combined treatment induced significantly the expression of the five members when compared to rats treated with Cur or VPA only as well as to self-recovery group, which indicates a possible benefit from the synergistic effect of Cur-VPA combination as therapeutic agents for neuroinflammation and its associated disorders. The mechanism elucidated here highlights the particular drug-induced expression profile of let-7 family as new targets for future pharmacological development.